Policing problem places crime hot spots and effective prevention - Braga, Anthony Allan, 1969-; Weisburd, David (New York ; Oxford : Oxford University Press, 2010)
There is good evidence that the police can control crime hot spots without simply displacing crime problems to other places. Police officers should strive to use problem-oriented policing and situational crime prevention techniques to address the place dynamics, situations, and characteristics.
Description based on online resource; title from home page (viewed Sept. 8, 2010).
Keywords: Problem-oriented policing; Crime prevention